2023
DOI: 10.3390/toxics11100874
|View full text |Cite
|
Sign up to set email alerts
|

The Application of a Physiologically Based Toxicokinetic Model in Health Risk Assessment

Mengting Chen,
Ruihu Du,
Tao Zhang
et al.

Abstract: Toxicokinetics plays a crucial role in the health risk assessments of xenobiotics. Classical compartmental models are limited in their ability to determine chemical concentrations in specific organs or tissues, particularly target organs or tissues, and their limited interspecific and exposure route extrapolation hinders satisfactory health risk assessment. In contrast, physiologically based toxicokinetic (PBTK) models quantitatively describe the absorption, distribution, metabolism, and excretion of chemicals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 124 publications
0
6
0
Order By: Relevance
“…4 Protein binding Binds to plasma proteins after the absorption into systemic circulation Protein-corona formation on their surface 50 Extrapolation Traditional route-to-route extrapolation approaches of PBPK models 65 Route-specific approach of PBPK models 65 models provide a more comprehensive approach in identifying the chemical concentrations in specific organs or tissues compared to the classical compartmental models. 70 PBTK models serve as valuable tools for extrapolating data and providing a theoretical foundation for health risk assessment and management. 70 The internal kinetics of nine chemicals (three endocrine disrupters, three liver steatosis inducers, and three developmental toxicants) were anticipated by using PBTK modeling in data-rich and data-poor conditions, and higher degrees of parametrization complexity were applied.…”
Section: Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Protein binding Binds to plasma proteins after the absorption into systemic circulation Protein-corona formation on their surface 50 Extrapolation Traditional route-to-route extrapolation approaches of PBPK models 65 Route-specific approach of PBPK models 65 models provide a more comprehensive approach in identifying the chemical concentrations in specific organs or tissues compared to the classical compartmental models. 70 PBTK models serve as valuable tools for extrapolating data and providing a theoretical foundation for health risk assessment and management. 70 The internal kinetics of nine chemicals (three endocrine disrupters, three liver steatosis inducers, and three developmental toxicants) were anticipated by using PBTK modeling in data-rich and data-poor conditions, and higher degrees of parametrization complexity were applied.…”
Section: Metabolismmentioning
confidence: 99%
“…70 PBTK models serve as valuable tools for extrapolating data and providing a theoretical foundation for health risk assessment and management. 70 The internal kinetics of nine chemicals (three endocrine disrupters, three liver steatosis inducers, and three developmental toxicants) were anticipated by using PBTK modeling in data-rich and data-poor conditions, and higher degrees of parametrization complexity were applied. 71 The results revealed that the parametrization significantly influences the outputs of the model since it can alter the prioritization of chemicals based on internal concentration factors.…”
Section: Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The FDA suggests that a relatively easy and promising approach to obtain such quantitative relationships is the use of modeling and simulation tools. ,, Physiologically based toxicokinetic (PBTK) models bear the capability to connect in vivo ion release with clinically measurable parameters such as ion concentrations in blood or urine. This allows for a direct comparison between the inferred in vivo exposure from these measurements and the outcomes of in vitro testing . Establishing such correlations necessitates a combination of computational modeling and in vitro , ex vivo , and in vivo testing and eventually clinical studies to parameterize and validate the model predictions.…”
Section: Introductionmentioning
confidence: 99%
“…This allows for a direct comparison between the inferred in vivo exposure from these measurements and the outcomes of in vitro testing. 34 Establishing such correlations necessitates a combination of computational modeling and in vitro , ex vivo , and in vivo testing and eventually clinical studies to parameterize and validate the model predictions. Although a number of studies have reported data regarding the concentration of different metal ions in serum and urine for healthy adults, 35 38 there is still limited information about the levels of released ions, especially their accumulation in tissues/organs following the in situ implantation of medical devices.…”
Section: Introductionmentioning
confidence: 99%